PROPOSITIONS OF DIDACTIC AND TECHNOLOGICAL RESOURCES BY MASTERS IN EDUCATION: A NECESSARY REFLECTION FOR TEACHING IN AND AFTER THE PANDEMIC - Souza, Mariana Aranha de; Bussolotti, Juliana Marcondes [UNESP]; Prospero da Cunha, Virginia Mara (Fundacao Univ Tocantins, 2022)
This text aims to present a reflection on the experiences of 39 Master's students in Education, entering the year 2021, who attended the elective course Didactic and Technological Resources in Teacher Training on the use of these resources in the context of Basic Education at and post pandemic. This is a qualitative study, in which two online questionnaires were used as instruments for data collection, one at the beginning of the course and another at the end, and the analysis of a technological educational product, proposed for the context of teacher training in and after a pandemic. The results showed that (a) there was already a previous experience of these master's students with the use of educational technologies, albeit at different levels of application; and (b) the collaborative work allowed an advance in the reflection on educational technologies and enabled the development of educational technological products to be implemented in the context of teacher training.
Keywords: Educational Technologies; Teacher Training; Professional Master's in Education; Education in and after the Pandemic